Deep-subwavelength magnetic-coupling-dominant interaction among magnetic localized surface plasmons - Gao, Zhen (2017)
Magnetic coupling is generally much weaker than electric Coulomb interaction. This also applies to the well-known magnetic “meta-atoms,” or split-ring resonators (SRRs) as originally proposed by Pendry et al. [IEEE Trans. Microwave Theory Tech. 47, 2075 (1999)], in which the associated electric dipole moments usually dictate their interaction. As a result, stereometamaterials, a stack of identical SRRs, were found with electric coupling so strong that the dispersion from merely magnetic coupling was overturned. Recently, other workers have proposed a new concept of magnetic localized surface plasmons, supported on metallic spiral structures (MSSs) at a deep-subwavelength scale. Here, we experimentally demonstrate that a stack of these magnetic “meta-atoms” can have dominant magnetic coupling in both of its two configurations. This allows magnetic-coupling-dominant energy transport along a one-dimensional stack of MSSs, as demonstrated with near-field transmission measurement. Our work not only applies this type of magnetic “meta-atom” into metamaterial construction, but also provides possibilities of magnetic metamaterial design in which the electric interaction no longer takes precedence.